2004
DOI: 10.1044/1092-4388(2004/056)
|View full text |Cite
|
Sign up to set email alerts
|

Separating Contributions of Hearing, Lexical Knowledge, and Speech Production to Speech-Perception Scores in Children With Hearing Impairments

Abstract: Open-set word and sentence speech-perception test scores are commonly used as a measure of hearing abilities in children and adults using cochlear implants and/or hearing aids. These tests are usually presented auditorily with a verbal response. In the case of children, scores are typically lower and more variable than for adults with hearing impairments using similar devices. It is difficult to interpret children's speech-perception scores without considering the effects of lexical knowledge and speech-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…Rate of receptive vocabulary acquisition in this group was 69% of that expected for a normally hearing child, average phoneme production scores were around 90%, and production error rates were approximately 8% higher than expected for age. This level of performance is consistent with previously reported findings for implanted youngsters (Blamey et al, 2001;Paatsch et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Rate of receptive vocabulary acquisition in this group was 69% of that expected for a normally hearing child, average phoneme production scores were around 90%, and production error rates were approximately 8% higher than expected for age. This level of performance is consistent with previously reported findings for implanted youngsters (Blamey et al, 2001;Paatsch et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
“…To date there is no other published data describing speech and language outcomes in implanted AN/AD children. Results for the implanted subject groups in this study and previously reported findings for hearing-impaired children (Blamey et al, 2001;Paatsch et al, 2004) do, however, indicate a link between spoken language development and speech perception ability, and there is growing evidence that a small proportion of AN/AD children will not obtain significantly improved perception of speech with a cochlear implant (Gibson & Sanli, 2007;Rance & Barker, 2007;Zeng & Lui, 2006). The development of techniques that can pre-operatively determine an individual's potential for benefit from cochlear implantation (such as recording EABRs via a trans-tympanic needle electrode placed on the cochlear promontory or round window) is an area of ongoing research.…”
Section: Discussioncontrasting
confidence: 50%
“…A possible explanation for the different result for OSW and sentences could be related to the nature of each speech perception test against the backdrop of linguistic competence. Linguistic competence has been found to have a significant effect on speech perception scores for hearing-impaired children (Cowan et al 1997;Blamey and Sarant 2002;Paatsch et al 2004). A monosyllabic word test requires that a child repeat the word as they perceive it, without necessarily understanding the meaning of the word.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are comparative studies examining the relationship between speech perception skills and speech development [70,71], this is one of the first studies to demonstrate on the impact of auditory intervention using a defined auditory hierarchy, on speech development. This prospective intervention study using speech perception tests scored independent of children's speech output is therefore an important contribution to the understanding of the impact of speech perception development on speech development.…”
Section: Speech Developmentmentioning
confidence: 98%